2011
DOI: 10.1001/archsurg.2010.299
|View full text |Cite
|
Sign up to set email alerts
|

Possible Geographical Barriers to Trauma Center Access for Vulnerable Patients in the United States

Abstract: Objective To study whether traditionally vulnerable populations have worse geographic access to trauma centers. Design A cross-sectional analysis using data from the American Hospital Association Annual Survey from 2005 linked with zip code–level data from the US Census. We used a multinomial logit model to examine the odds of having difficult as opposed to easy access to trauma centers for a given subgroup of vulnerable populations. Setting and Participants Population in rural and urban communities as def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 40 publications
4
86
1
Order By: Relevance
“…Due to the geographic distribution of various demographic groups in the US, this disparity may disproportionately impact racial minorities and people living in poverty. 6 Little is known about the causal pathway for this disparity. Time to treatment is presumed to be a significant factor in trauma outcomes, 41 and would disparately impact rural populations, 5,6 but evidence for the relationship between pre-hospital time and mortality is widely variable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the geographic distribution of various demographic groups in the US, this disparity may disproportionately impact racial minorities and people living in poverty. 6 Little is known about the causal pathway for this disparity. Time to treatment is presumed to be a significant factor in trauma outcomes, 41 and would disparately impact rural populations, 5,6 but evidence for the relationship between pre-hospital time and mortality is widely variable.…”
Section: Discussionmentioning
confidence: 99%
“…6 Little is known about the causal pathway for this disparity. Time to treatment is presumed to be a significant factor in trauma outcomes, 41 and would disparately impact rural populations, 5,6 but evidence for the relationship between pre-hospital time and mortality is widely variable. 30,32,[42][43][44][45][46][47][48][49][50][51][52] Other factors, such as community-level wealth and insurance coverage, [53][54][55] may also contribute to geographic disparities in injury mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, there are concerns regarding how the limited availability of surgical specialists in rural areas might impact outcomes in emergent conditions such as trauma or hip fracture when the time to presentation and treatment is important. This issue was highlighted in an article by Hsia and Shen [15] (with a comment by Dimick [10]), who reported that more than 38 million Americans did not have access to a trauma center within a 1-hour drive. Our investigation suggests that although rural patients with fractures do need to travel farther, they do not appear to have worse outcomes because of this need to travel.…”
Section: Discussionmentioning
confidence: 99%